2004
DOI: 10.1007/s00125-004-1461-0
|View full text |Cite
|
Sign up to set email alerts
|

Night-time restricted feeding normalises clock genes and Pai-1 gene expression in the db/db mouse liver

Abstract: Aims/hypothesis. An increase in PAI-1 activity is thought to be a key factor underlying myocardial infarction. Mouse Pai-1 (mPai-1) activity shows a daily rhythm in vivo, and its transcription seems to be controlled not only by clock genes but also by humoral factors such as insulin and triglycerides. Thus, we investigated daily clock genes and mPai-1 mRNA expression in the liver of db/db mice exhibiting high levels of glucose, insulin and triglycerides. Methods. Locomotor activity was measured using an infrar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
79
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 42 publications
13
79
2
2
Order By: Relevance
“…Kohsaka et al [13] reported that a high-fat diet lengthened the period of locomotor activity rhythm under constant darkness in mice, but the effect was not detected under a 12-h light/12-h dark cycle. Moreover, night-time restricted feeding can normalize the impaired circadian clock in the livers of db/db mice [34]. These results suggest Consistent with the intact intracellular clock, the daily expression rhythms of most circadianly expressed genes examined were preserved in the livers of mice with NASH.…”
Section: Methodsmentioning
confidence: 56%
“…Kohsaka et al [13] reported that a high-fat diet lengthened the period of locomotor activity rhythm under constant darkness in mice, but the effect was not detected under a 12-h light/12-h dark cycle. Moreover, night-time restricted feeding can normalize the impaired circadian clock in the livers of db/db mice [34]. These results suggest Consistent with the intact intracellular clock, the daily expression rhythms of most circadianly expressed genes examined were preserved in the livers of mice with NASH.…”
Section: Methodsmentioning
confidence: 56%
“…At 9 wk of age, they were divided into two groups, one continuously housed as stated above (control) and the other subjected to 1 wk of unpredictable CMS. At 10 wk of age, 24 mice of each strain were killed by cervical dislocation at 6-h intervals over 24 h (2,4,28,46) to obtain liver and brain samples at zeitgeber times (ZTs) 3, 9, 15, and 21 in which ZT 0 is defined as lights on and ZT 12 as lights off (n ϭ 6/group for each observation point). All animal studies were conducted in accordance with the institutional guidelines for animal experiments and were approved by Tohoku University.…”
Section: Methodsmentioning
confidence: 99%
“…Genetically obese strains such as KK-Ay (3) and db/db mice (28), and mice with high-fat diet-induced obesity (27), exhibit attenuated circadian expressions of several clock genes in the liver. Intriguingly, in all of these murine models, serum corticosterone levels were shown to be altered (1,27).…”
Section: E305 Chronic Stress Perturbs Hepatic Clockmentioning
confidence: 99%
“…For example, sleep deprivation has been shown to shift the circadian clock, even when stress and overall activity levels have been controlled [49]. In murine models of obesity and diabetes, it is common to find attenuated rhythms of food intake, locomotor activity, and body temperature [50][51][52][53]. Intriguingly, when db/db mice, Zucker obese rats, and H1 receptor deficient mice are provided with food only during the dark phase, their increase in weight gain is attenuated, locomotor rhythms are improved, and other altered metabolic parameters show improvement [50][51][52].…”
Section: Anatomical Model Of Scn Out Signalingmentioning
confidence: 99%
“…In murine models of obesity and diabetes, it is common to find attenuated rhythms of food intake, locomotor activity, and body temperature [50][51][52][53]. Intriguingly, when db/db mice, Zucker obese rats, and H1 receptor deficient mice are provided with food only during the dark phase, their increase in weight gain is attenuated, locomotor rhythms are improved, and other altered metabolic parameters show improvement [50][51][52]. The ability of a high fat diet to induce weight gain is prevented when rats are fed only during the primary eating phase, the dark period [54].…”
Section: Anatomical Model Of Scn Out Signalingmentioning
confidence: 99%